Effect of surface treatments on biaxial flexural strength, fatigue resistance, and fracture toughness of high versus low translucency zirconia - Alaaeldin Elraggal; Moustafa Aboushelib; Islam M. Abdel Raheem; Rania R. Afifi (BMC, 2022)
Abstract Background Mechanical surface treatments can deteriorate the mechanical properties of zirconia. This study evaluated and compared the biaxial flexural strength, fracture toughness, and fatigue resistance of high translucency (HT) to low translucency (LT) zirconia after various mechanical surface treatments. Methods Four hundred eighty zirconia discs were prepared by milling and sintering two HT (Katana and BruxZir) and LT (Cercon and Lava) zirconia blocks at targeted dimensions of 12 mm diameter × 1.2 mm thickness. Sintered zirconia discs received one of the following surface treatments: low-pressure airborne particle abrasion (APA) using 50 µm alumina particles, grinding using 400 grit silicon carbide paper, while as-sintered specimens served as control. Internal structure and surface roughness were evaluated by scanning electron microscope (SEM) and a non-contact laser profilometer, respectively. Half of the discs were tested for initial biaxial flexural strength, while the rest was subjected to 106 cyclic fatigue loadings, followed by measuring the residual biaxial flexural strength. Fractured surfaces were examined for critical size defects (c) using SEM to calculate the fracture toughness (KIC). The effect of surface treatments, zirconia type, and cyclic fatigue on the biaxial flexural strength was statistically analyzed using three-way analysis of variance (ANOVA) and Tukey HSD post hoc tests (α = 0.05). Weibull analysis was done to evaluate the reliability of the flexural strength for different materials. Results The initial biaxial flexural strength of LT zirconia was significantly higher (p < 0.001) than that of HT zirconia in all groups. While low APA significantly increased the biaxial flexural strength of LT zirconia, no significant change was observed for HT zirconia except for Katana. Surface grinding and cyclic fatigue significantly reduced the flexural strength of all groups. High translucency zirconia reported higher fracture toughness, yet with lower Weibull moduli, compared to LT zirconia. Conclusion LT zirconia has higher biaxial flexural strength, yet with lower fracture toughness and fatigue resistance, compared to HT zirconia. Low-pressure APA has significantly increased the biaxial flexural strength in all zirconia groups except BruxZir. Grinding was deteriorating to biaxial flexural strength and fracture toughness in all zirconia types. Cyclic fatigue has significantly decreased the biaxial flexural strength and reliability of HT and LT zirconia.